2023
DOI: 10.1111/padr.12553
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Approach to Family Life Course Change across 1930–1978 Chinese Birth Cohorts

Abstract: Family formation in China has undergone dramatic changes. Despite increasing academic attention, few studies have taken a holistic approach to study cohort change in Chinese family life courses. In this study, we assess how family life course patterns and diversity changed across 1930-1978 birth cohorts. Moreover, we evaluate to what extent changing norms, economic constraints, and institutional reforms drove cohort differences. Data from the China Family Panel Studies and sequence analysis are applied to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 82 publications
3
1
0
Order By: Relevance
“…Similarly, by focusing only on youth life trajectories from ages 16-24, it may not capture the full trajectory of adulthood transitions that continue beyond the age of 24. However, in supporting our findings, a recent related study employing a broader age range and including birth cohorts before 1978 found that urban hukou origin was associated with less diverse life courses (Van Winkle and Wen, 2023). Future research could explore whether the rural-urban divide persists for more recent cohorts, like those we have considered in our study.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Similarly, by focusing only on youth life trajectories from ages 16-24, it may not capture the full trajectory of adulthood transitions that continue beyond the age of 24. However, in supporting our findings, a recent related study employing a broader age range and including birth cohorts before 1978 found that urban hukou origin was associated with less diverse life courses (Van Winkle and Wen, 2023). Future research could explore whether the rural-urban divide persists for more recent cohorts, like those we have considered in our study.…”
Section: Discussionsupporting
confidence: 86%
“…First, it reveals that China's post-1980s and post-1990s generations of rural youth experience more diverse or de-standardized pathways from adolescence to early adulthood compared to their urban counterparts. This study thus aligns with recent comparative literature to challenge the prevailing assumption that transition to adulthood pathways mimic the Western model: that is, the transition pathway becoming more diversified first in developed regions, a pattern which then spreads to developing regions driven by ideational changes (Van Winkle, 2018;Van Winkle and Wen, 2023). Instead, in the Chinese context, the de-standardization of rural youths' pathways to adulthood likely stems from a scarcity of resources in their families and communities, coupled with elevated economic uncertainties and institutional setting that divide the rural and urban population, rather than from ideational changes suggested by the second demographic transition theory.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations